Lessons learned in application driven imaging agent design for image-guided surgery. - Buckle, Tessa; Rietbergen, Daphne D. D.; de Wit -van der Veen, Linda; Schottelius, Margret (European Journal of Nuclear Medicine & Molecular Imaging, 2024)
To meet the growing demand for intraoperative molecular imaging, the development of compatible imaging agents plays a crucial role. Given the unique requirements of surgical applications compared to diagnostics and therapy, maximizing translational potential necessitates distinctive imaging agent designs. For effective surgical guidance, exogenous signatures are essential and are achievable through a diverse range of imaging labels such as (radio)isotopes, fluorescent dyes, or combinations thereof. To achieve optimal in vivo utility a balanced molecular design of the tracer as a whole is required, which ensures a harmonious effect of the imaging label with the affinity and specificity (e.g., pharmacokinetics) of a pharmacophore/targeting moiety. This review outlines common design strategies and the effects of refinements in the molecular imaging agent design on the agent's pharmacological profile. This includes the optimization of affinity, pharmacokinetics (including serum binding and target mediated background), biological clearance route, the achievable signal intensity, and the effect of dosing hereon.